Relationship between Workplace Learning and Sustainable Lean Implementation with Continuous Improvement as Mediator : A Study of Lean Manufacturing in Malaysia - Lim, Agnes, Siang Siew (Universiti Malaysia Sarawak (UNIMAS), 2019)
The objective of this study is to identify the relationship between employee’s perception towards workplace learning and sustainable Lean implementation with the presence of continuous improvement as a mediator in Lean manufacturing companies in Malaysia. In response to Resource Based Theory (RBT), this study fulfils the need to identify the characteristics (learning) and unique capabilities (continuous improvement) that must be possess by the resources (employees) to create value rather than merely identifying the type of resource in order to sustain competitive advantage in Lean firms. This study adopted quantitative research approach suitable for descriptive human resource development research. The design of this study is in the form of cross-sectional study. Survey questionnaire is utilized as the instrument for data collection. Eight Lean manufacturing companies located in Malaysia participated in this study which contributed to a total of 219 collectable gains. All the empirical findings obtain through a series of hypothesis testing achieved the sufficient level of significance to support the presence of mediator of this study, which is continuous improvement influenced the relationship between the predictor variable, which is workplace learning and the dependent variable, which is sustainable Lean implementation. However, Simple Linear Regression result shows that continuous improvement partially mediates the relationship between continuous learning and sustainable Lean implementation. Besides, the result of Pearson Correlation shows that there is a significantly strong positive relationship between embedded systems and sustainable Lean implementation. From the support of empirical findings, this study intends to serve as guidelines for practitioners to develop a more solid roadmap for Lean implementation.